ANALISIS MINAT BELAJAR SISWA TERHADAP MATA PELAJARAN FISIKA DI SMA NEGERI 1 SAKTI - Hamdi Cut Kurniawati Rahim (Jurnal Sains Riset, 2020)
The study, entitled "Analysis of Student Learning Interest in Physics Subjects in SMA Negeri 1 Sakti" raises the issue of how students' interest in learning at SMA Negeri 1 Sakti is towards physics. This study aims to measure the extent of the interest of students of SMA Negeri 1 Sakti towards physics. The subjects in this study were students majoring in Natural Sciences class XI MIPA1 in SMA Negeri 1 Sakti, the object of this study was the interest in learning for students of class XI MIPA1 in SMA Negeri 1 Sakti. The method used is a case study research method with a qualitative approach. Data collection was carried out using questionnaire delivery techniques for students and data processing was carried out using Analysis Interactive models from Miles and Huberman. After all, the result of data were presented in some precentages. Based on the results of data analysis of each indicator of interest it was found that overall XI MIPA1 students in SMA Negeri 1 Sakti had an interest in physics with an average percentage score of 48.4%. Interest in teachers with an average percentage score of 54.9%. There are goals to be achieved for the future with an average percentage of a score of 40.9%. Success in learning with an average percentage score of 72.8%. Finding benefits in the learning process with an average percentage of 70.6%. Have the initiative to learn with an average percentage of 72.8%. Concentration in learning with an average percentage score of 77.3%. Willingness in learning with an average percentage score of 81.8%. Based on the results of the analysis shows that students in SMA Negeri 1 Sakti have a good interest in physics. It is recommended that research related to the analysis of students' learning interest at the SMA / MA level and at the SMP / Mts level be continued by other researchers so that things that have not been revealed in this study can be revealed Keywords: Analysis of student learning interst, questionnaire, physics